Barriers to HIV care among Francophone African, Caribbean and Black immigrant people living with HIV in Canada: A protocol for a scoping systematic review - Djiadeu, Pascal; Nguemo, Joseph; Mukandoli, Chantal; Odhiambo, Apondi. J.; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2019)
Introduction Language is a social determinant of health. Addressing social determinants of health is paramount to successful progression along the HIV-care continuum. Canada is a bilingual country with French and English as official languages. There are few studies to date that have focused on the impact of being a French-speaking linguistic minority on the HIV-care continuum. The primary objective of this scoping, systematic review of literature is to evaluate existing gaps in access to HIV- care among French-speaking people living with HIV in Canada. Our primary outcome is healthcare services availability and access for French- speaking people living with HIV. Methods and analyses Our scoping, systematic review will draw on a systematic search of published literature, both quantitative and qualitative studies published on French-speaking individuals' healthcare and HIV status in Canada, with particular emphasis on the province of Ontario. We will conduct our search in MEDLINE, the Excerpta Medica Database, the Cumulative Index to Nursing and Allied Health Literature, Web of Science, EBSCO and Google Scholar for work published between 1990 and 2018. Identified articles will be screened in duplicate and full-text articles of relevant studies will be retrieved. Data will also be extracted by two researchers working independently. Any discrepancies that arise will be resolved by consensus or by consulting a third author. Our findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Ethics and dissemination Our proposed research will not be conducted with human participants. We will only use secondary published data and therefore ethics approval is not required. Our findings will be disseminated as peer reviewed manuscripts at conferences and student rounds, and could be of interest to government health agencies and local HIV/AIDS service organisations.

Pratique # 1 : Le Guide de mise en œuvre du mandat linguistique d’Actionmarguerite (Manitoba). - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2019)
Entre 2011 et 2013, en collaboration avec la SSF, le Conseil Communauté en santé du Manitoba et d’autres partenaires, Actionmarguerite a participé à un projet qui a permis de mieux comprendre la situation actuelle des services aux aînés francophones, puis d’agir pour améliorer la situation et enfin de transférer les connaissances afin que d’autres organisations puissent profiter de l’expérience acquise. La participation à ce projet témoigne de la valeur accordée par Actionmarguerite à l’innovation dans l’offre de services dans la langue officielle choisie par l’usager. C’est dans le cadre de cette initiative que le Guide de mise en œuvre du mandat linguistique d’Actionmarguerite, un guide bilingue à l’intention des gestionnaires a été conçu. Ce guide rappelle le contexte juridique en matière de langues de services et intègre les principaux documents qui encadrent la langue des services à l’échelle de la province, de l’ORSW et d’Actionmarguerite. Il précise les responsabilités des gestionnaires afin de s’assurer que les clients francophones soient servis dans la langue de leur choix.